Implementasi Metode Topsis Untuk Menentukan Karyawan Terbaik Pada Bengkel dan Variasi TJM Pringsewu - Nungsyati, Nungsyati; Primeidila, Asifa; Muslihudin, Muhamad (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2025)
This research was conducted at Bengkel dan Variasi TJM Pringsewu, which provides car maintenance and customization services. The main objective of this study is to apply the TOPSIS method in determining the best employee through a mobile web-based platform. The TOPSIS method was chosen for its ability to provide objective and systematic assessments based on five criteria: Teamwork, Work Results, Discipline, Skills, and Work Ethics. Data were collected through observation, interviews, and literature studies. The analysis results show that alternative A11 was selected as the best employee with the highest score, both through manual calculation and using Excel. The system proved to be fast and accurate in the assessment process, making the implementation of TOPSIS effective in supporting employee performance improvement.